Impacts, Challenges, And Opportunities Of Rohingya Immigrants For Aceh's Regional Economy And Indonesia's National Security - Khairul Rizqiah; Jonni Mahroza; Muliahadi Tumanggor; Suwito, Suwito; Sri Murtiana; Sri Patmi; Lukman Yudho Prakoso (CV. AFDIFAL MAJU BERKAH, 2024)
The fundamental problem of Rohingya immigrants coming to Indonesia in large numbers has been a hotly debated issue in recent years. Rohingya immigrants are a group of ethnic minorities from Rakhine state, Myanmar. They have experienced discriminatory treatment that has caused them to flee Myanmar and seek safety in other countries, including Indonesia. The arrival of immigrants to Indonesia has the potential to impact the regional economy of Indonesia's national security. The regional economy is an economic activity carried out by economic actors (households, companies, and government) in a region to meet the needs of its people. Meanwhile, national security is an effort and strategy undertaken by the state to protect the integrity, sovereignty and sustainability of life and aims to ensure the safety and security of the state. In resolving national security through diplomacy between countries. For Indonesia, this is very important to achieve national development and ensure the safety and welfare of the community. The purpose of this study is to analyze the impact of the arrival of Rohingya immigrants on Indonesia's national security, the impact can be in the form of threats or opportunities, in this case government policies to deal with the problem. This research uses a systematic literature review method with national and international approaches. This is to draw conclusions from several previous studies related to Rohingya immigrants: Threat or opportunity for Indonesia's national security. It is hoped that this research can provide a reference to the government in determining policies related to Rohingya immigrants for Indonesia's national security.